Is there a film in this text? The commercial success of Rubem Fonseca's cinematic literature - Lopes, Helena Isabel da Silva (2021)
This dissertation focuses on the language of film in Rubem Fonseca’s literary fiction. Fonseca’s literature’s complicity with the language of cinema is examined through the appropriation of mass film narrative conventions, the observance of screenplay guidelines and the literary recreation of an illusionist rhetoric of film characterized by fluidity, transparency and immediacy. Effective in producing speed and readability, Fonseca’s assimilation of a cinematic rhetoric subsumable in David Bordwell’s notion of continuity system constitutes a cornerstone of his modality of literary realism, sometimes capable of producing effects of real. Unveiled by means of a transmedial and intercultural approach, the psychological operations of mental imagery during the consumption of this intermedial artifact classified as cinematic literature in the age of post-cinema are described. Fueled by cinema, the accessibility of Fonseca’s broadbrow fiction is framed in a postmodernist protocol of reading capable of crossing the border between high and lowbrow audiences, thus closing a sociologic gap between elites and masses. After assessing the commercial success of Fonseca’s books in Portugal and Brazil, the monography proceeds to exhort publishing houses to extend the marketing of his books to low and middlebrow audiences, with a view to fulfilling the sales potential this research finds in Fonseca’s ingeniously salable transmedial recipe. A strategy for the measurement of the author’s value as an intangible asset of Sextante, Rubem Fonseca’s Portuguese publishing house, is proposed. The microeconomic benefits of such monetization of Intellectual Capital for the company are highlighted. The benefits of increasing the sales of Fonseca’s broadbrow literature at the macroeconomic level are also emphasized with regard to the generation of wealth and increase of sustainability through the extension of literacy.